Estimating aboveground biomass of logged forest in Terengganu using lidar and ground based measurement - Lina Farhana Ab. Karim, 1991-, author; Kasturi Devi Kanniah; Fakulti Geoinformasi dan Harta Tanah (2015)
Project Paper (Sarjana Muda Sains (Geoinformatik)) - Universiti Teknologi Malaysia, 2015